A 1.58 nW power consumption and 34.45 ppm/°C temperature coefficient bandgap reference (BGR) for subblocks of RFID tag. Issue 5 (May 2015) - Salehi, Mohammad Reza; Dastanian, Rezvan; Abiri, Ebrahim; Nejadhasan, Sajad
Abstract In this paper a bandgap reference (BGR) circuit irrespective of the temperature and the supply voltage variation with very low power consumption is proposed. The proportional to absolute temperature (PTAT) and complementary to absolute temperature (CTAT) generators of the proposed BGR, which has four cores cascaded with each other, are used in order to increase not only the output voltage, but also the output control ability for the temperature and the voltage insensitivity. To combine produced voltage from PTAT and CTAT generator, a weight combination circuit, which uses internal capacitors of transistors, is applied. Due to the fact that all of the transistors in such a topology are worked in sub-threshold region, the power consumption is significantly diminished to 1.58 nW. Also the variation of the temperature from −25 °C to 150 °C, leads to the temperature coefficient about 34.45 ppm/°C. The design simulation is done at 960 MHz frequency in TSMC 0.18 µm CMOS technology with the help of Cadence software. Also the post layout simulation result and the layout of the proposed circuit are presented. The output and the chip area of this BGR are 141.5 mV and 1387 µm2 respectively.